2010
DOI: 10.1161/circinterventions.109.890053
|View full text |Cite
|
Sign up to set email alerts
|

Major Predictors of Long-Term Clinical Outcomes After Coronary Revascularization in Patients With Unprotected Left Main Coronary Disease

Abstract: Background-The clinical characteristics that identify high-risk subsets of patients with unprotected left main coronary artery disease undergoing percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) have not been well established. Methods and Results-Between January 2000 and June 2006, 2240 patients with unprotected left main coronary artery disease underwent PCI (nϭ1102) or CABG (nϭ1138). Twenty-six preprocedural parameters were evaluated by univariate and multivariate Cox regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 39 publications
(38 reference statements)
2
28
0
3
Order By: Relevance
“…Similar to previous reports involving multivessel CAD treated with PCI or CABG, [18][19][20][21] we found that renal insufficiency, low EF, age, and diabetes mellitus were the strongest predictors of MACCE and all-cause mortality in patients with ULMCA disease. In addition to these strongest predictors, other key predictors of major clinical events or death were peripheral vascular disease, atrial fibrillation, chronic lung disease, previous stroke, acute coronary syndrome, or high body mass index.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous reports involving multivessel CAD treated with PCI or CABG, [18][19][20][21] we found that renal insufficiency, low EF, age, and diabetes mellitus were the strongest predictors of MACCE and all-cause mortality in patients with ULMCA disease. In addition to these strongest predictors, other key predictors of major clinical events or death were peripheral vascular disease, atrial fibrillation, chronic lung disease, previous stroke, acute coronary syndrome, or high body mass index.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, as previously reported, 14,20,21 our study demonstrated that low e-GFR<60, DM, high EuroScore, and low EF were significantly associated with long-term cardiac-mortality. Furthermore, presence of residual CTO-RCA played a significant important role in the cardiac-mortality among the other anatomic information.…”
Section: Discussionsupporting
confidence: 88%
“…• The EuroSCORE validated to predict surgical mortality was recently shown to be an independent predictor of major adverse cardiac events (MACEs) in studies with both percutaneous and surgical treatment arms [2,3]. Therefore, it can be used to determine the risk of revascularization irrespective of, and even before, the selection of treatment strategy.…”
Section: Scores and Risk Stratification Impact Of Comorbiditymentioning
confidence: 99%